Improving Response Rates to an Alumni Survey in East Africa - Mwizerwa, Joseph; Robb, Walter; Namukwaya, Carolyne; Mary Namuguzi, Mary; Brownie, Sharon (Advances in Social Sciences Research Journal, 2017)
Feedback from students and graduates is essential to inform ongoing quality improvement in higher education. However, African universities often face implementation issues in alumni surveys, including technological barriers and difficulties in tracking graduates, particularly those from earlier cohorts and rural alumni. Innovative strategies are needed to locate alumni and obtain a good response rate across widely dispersed, rural and remote areas. This paper reports on strategies used to increase response rates in an East African online alumni survey in a context of limited computer/Internet access. The survey aimed to assess the impact of nursing graduates over a 15 year period (2001–2016). Strategies focused on locating and communicating with graduates and providing solutions to barriers associated with computer/Internet access. Better engagement with alumni was achieved using mobile technologies and social media networks. Facilitating access to online surveys by taking technology to alumni or providing hubs for online access encouraged survey participation. The strategies discussed in this study are particularly relevant for clustered or networked alumni populations (e.g. nurses) in low income and limited resource settings.